COEVOLUTIONARY SEMANTICS OF TECHNOLOGICAL CIVILIZATION GENESIS AND EVOLUTIONARY RISK (BETWEEN THE BIOAESTHETICS AND BIOPOLITICS) - V. T. Cheshko; O. M. Kuz (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose (metatask) of the present work is to attempt to give a glance at the problem of existential and anthropological risk caused by the contemporary man-made civilization from the perspective of comparison and confrontation of aesthetics, the substrate of which is emotional and metaphorical interpretation of individual subjective values and politics feeding by objectively rational interests of social groups. In both cases there is some semantic gap present between the represented social reality and its representation in perception of works of art and in the political doctrines as well. Methodology of the research is evolutionary anthropologicalcomparativistics. Originality of the conducted analysis comes to the following: As the antithesis to biological and social reductionism in interpretation of the phenomenon of bio-power it is proposed a co-evolutionary semantic model in accordance with which the described semantic gap is of the substantial nature related to the complex module organization of a consistent and adaptive human strategy consisting of three associated but independently functional modules (genetic, cultural and techno-rational). Evolutionary trajectory of all anthropogenesis components including civilization cultural and social-political evolution is identified by the proportion between two macro variables – evolutionary effectiveness and evolutionary stability (sameness), i.e. preservation in the context of consequential transformations of some invariants of Homo sapiens species specificity organization. It should be noted that inasmuch as in respect to human, some modules of the evolutionary (adaptive) strategy assume self-reflection attributes, it would be more correctly to state about evolutionary correctness, i.e. correspondence to some perfection. As a result, the future of human nature depends not only on the rationalist principles of ethics of Homo species (the archaism of Jurgen Habermas), but also on the holistic and emotionally aesthetic image of «Self». In conclusion it should be noted that there is a causal link between the development of High Hume (NBIC) technologies and the totality of the trend in the anthropological phenomenon of bio-power that permeates all the available human existence in modern civilization. As a result, there is a transformation of a contemporary social (man-made) risk in the evolutionary civilization risk.